2015
DOI: 10.1039/c5ra13415c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced rhamnolipid production of Pseudomonas aeruginosa SG by increasing copy number of rhlAB genes with modified promoter

Abstract: Increasing the copy number of rhlAB genes with a modified promoter efficiently enhanced the production of rhamnolipid by P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Although much effort has been invested in heterologous expression of rhl AB, the pathogenic strain P . aeruginosa PAO1 remains the best producer of rhamnolipids (Zhao et al., 2015). To evaluate the safety of an attenuated P .…”
Section: Resultsmentioning
confidence: 99%
“…Although much effort has been invested in heterologous expression of rhl AB, the pathogenic strain P . aeruginosa PAO1 remains the best producer of rhamnolipids (Zhao et al., 2015). To evaluate the safety of an attenuated P .…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether an increase in the gene dosage discussed above was sufficient to confer the adenosine growth variant phenotype, we used the plasmid pBBR1MCS-5 (44) to increase the gene copy number of the 6-kb region common to all variants. Pseudomonas aeruginosa contains approximately 5 copies of this plasmid per cell (45). We cloned the region encompassing PA0143 to PA0148 into pBBR1MCS-5 (see Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…It had been shown that a simple increment in the copy number of rhlAB under the control of indigenous strong promoter of oprL in P. aeruginosa SG could raise the rhamnolipid titer to 20.98 g/l [ 47 ]. Similarly, the overexpression of rhlAB under tac promoter in B. kururiensis increased the rhamnolipid titer from 0.78 to 5.76 g/l [ 48 ].…”
Section: Application Of Various Strategies To Increase Rhamnolipid Yimentioning
confidence: 99%